Deactivation and regeneration of hopcalite catalyst for carbon monoxide oxidation: a review - Dey S.; Dhal G.C. (My University, 2025)
Deactivation of hopcalite (CuMnOx) catalysts at carbon monoxide oxidation is a unique problem that causes loss of catalytic activity with time. The deactivation was done by the chemical, mechanical, thermal, poisoning, fouling, thermal degradation, vapor-solid formation, solid-solid reactions, and attrition/crushing processes. This review focuses on the mechanisms, prevention, control, and treatment of deactivation of hopcalite catalyst. The effect of various poisons and how they can influence the course of hopcalite catalytic reaction are described. Hopcalite catalyst deactivation is more easily prohibited than cured. Carbon deposition, coking, and moisture are the main causes of hopcalite catalyst deactivation. Sintering is best avoided by minimizing and controlling the temperature of reaction. Hopcalite catalyst regeneration is mainly recovering activity loss because of rapid coking or longer term deactivation associated with the loss of active metal dispersion. The addition of noble metals such as Au or Ag in hopcalite catalysts improved the activity and stability of catalysts and reduces their deactivation. The regeneration of deactivated catalysts is mainly depending upon the chemical, economic, and environmental factors. © 2019 Elsevier Ltd